Menjaga Spiritualitas Santri di Era AI: Antara Kemajuan Teknologi dan Ketahanan Nilai Islam - Rizqiyatul Muqorinah; Mufti Faqih Ali (At-Tadris: Journal of Islamic Education, 2025)
Artificial Intelligence (AI) has emerged in our midst, bringing a profound impact on various aspects of life, including religious education such as pesantren (Islamic boarding schools). As an Islamic educational institution responsible for shaping the character and spirituality of santri (students), pesantren faces both significant challenges and opportunities in adopting AI. This study aims to analyze the impact of AI technology implementation on the spiritual values and character of santri. The research follows a qualitative-descriptive model, which seeks to understand and describe phenomena in depth based on data collected from a natural setting. On the other hand, AI also poses challenges, such as reduced social interactions, shifts in mindset, and the risk of traditional pesantren values being eroded due to dependence on AI-driven technology. Therefore, strategic measures are necessary to ensure that the use of AI in education does not alter the spiritual values and character of santri.